Cytotoxicity of acetylcholinesterase reactivators evaluated in vitro and its relation to their structure. (4th May 2019) - Muckova, Lubica; Pejchal, Jaroslav; Jost, Petr; Vanova, Nela; Herman, David; Jun, Daniel
Abstract: The development of acetylcholinesterase reactivators, i.e., antidotes against organophosphorus poisoning, is an important goal of defense research. The aim of this study was to compare cytotoxicity and chemical structure of five currently available oximes (pralidoxime, trimedoxime, obidoxime, methoxime, and asoxime) together with four perspective oximes from K-series (K027, K074, K075, and K203). The cytotoxicity of tested substances was measured using two methods – colorimetric 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-tetrazolium bromide assay and impedance based real-time cytotoxicity assay – in three different cell lines (HepG2, ACHN, and NHLF). Toxicity was subsequently expressed as toxicological index IC50 . The tested compounds showed different cytotoxicity ranging from 0.92 to 40.06 mM. In HepG2 cells, K027 was the least and asoxime was the most toxic reactivator. In ACHN and NHLF cell lines, trimedoxime was the compound with the lowest adverse effects, whereas the highest toxicity was found in methoxime-treated cells. The results show that at least five structural features affect the reactivators' toxicity such as the number of oxime groups in the molecule, their position on pyridinium ring, the length of carbon linker, and the oxygen substitution or insertion of the double bond into the connection chain. Newly synthetized oximes with IC50 ≥ 1 mM evaluated in this three cell lines model might appear suitable for further testing.